Study of short polystyrene monolith-fritted micro-liquid chromatography columns for analysis of neutral and basic compounds - Legido-Quigley, C; Smith, N.W (Journal of Chromatography A, 2004)
This study details the effects of poly(styrene-divinylbenzene) (PS-DVB) frits in micro-HPLC columns for the separation of neutral and basic compounds. The procedure comprised the optimization of separations with only monolith or conventional fritted columns followed by method transference to short monolith-fritted columns. It was observed that a superior separation was achieved with the new columns compared to silica-fritted-packed columns once triethylamine (TEA) was added in small percentages. The separation of basic and neutral compounds was achieved in fast analysis times in the isocratic mode.